Prevalence and outcome of increased nuchal translucency in usmanu danfodiyo university teaching hospital, Sokoto, Nigeria: A cohort study - Sulaiman, B; Shehu, C; Panti, A; Saidu, S; Onankpa, B; Ekele, B (Nigerian journal of clinical practice, 2020)
Background: An important component of the first-trimester scan is nuchal translucency thickness at 11 weeks to 13 weeks 6 days of gestation. A nuchal translucency ≥3.3 mm is a significant early pregnancy scan finding associated with Trisomies 13, 18, and 21 and congenital heart diseases. Aims: To determine the prevalence and outcome of increased fetal nuchal translucency among pregnant women. Subjects and Methods: A prospective cohort study at the Obstetrics and Gynaecology Department of Usmanu Danfodiyo University Teaching Hospital Sokoto. This was a prospective study of 265 consecutively recruited women in the first trimester of pregnancy who presented to antenatal clinics over a 20-week period. An NT scan was conducted at 11 weeks to 13 weeks 6 days followed by an anomaly scan at 18-22 weeks. Patients were followed up to delivery and 6-week post-partum. The neonates were examined at delivery and at 6-week postnatal life. Data entry and analysis was done with IBM SPSS version 20. The level of significance was set at less than 0.05. Frequency distribution; student t-test and Chi-squared test. Results: The 95th percentile NT was 3.3 mm and the prevalence of increased NT above 3.3 mm was 3%. The mean maternal age of the participants was 28.1 ± 5.1 years and the modal parity was Para 0. The most common anomalies associated with increased NT were ventricular septal defect and spina bifida. A congenital anomaly was significantly associated with increased NT (P < 0.001). Conclusions: The prevalence of increased fetal nuchal translucency is relatively high in our environment and is associated with congenital fetal defects. Routine screening with first-trimester ultrasound will help detect congenital anomalies early.